Cognitive Determination of Musical Thinking and Musical Self-concept of Students and Musicians: Comparative Diagnostics, Aspects of Modeling and Forecasting - Mazur, Iryna; Нrinchenko, Tеtіana; Teplova, Olena; Onofrichuk, Liudmyla; Priadko, Olena (Harmonia: Journal of Arts Research and Education, 2022)
The article’s purpose is to define the cognitive determination of musical thinking and musical self-concept of students and musicians, considering the cognitive style of the individual, analytical-holistic thinking, and individual psychological abilities. The study applies the diagnostic technique for the cognitive style of individuality (T. Dudnikova, O. Volkova), analysis-holism scale (Choi, Koo, and Choi), Cattell test (16PF - C), musical thinking questionnaire developed by authors (I. Mazur, T. Нrinchenko, O. Teplova, L. Onofrichuk, O. Priadko). The study presents the first approbation of the musical thinking questionnaire developed by the authors, the integral indicator of which is measured on the following scales: emotional response to music, emotional-intonational (melodic) ear, harmonic ear for music, perceptual ear for music, musical-rhythmic sense, musical memory, performing emotionality, musical-creative imagination – insight into the essence of the musical image, musical-creative imagination – interpretation of the musical image, sense of the whole – sense of tempo-rhythm, sense of the whole – a sense of shape, sense of the whole – sense of style, sense of the whole – the sense of the logical development of the piece of music, cognitive activity, self-regulation, ability to work. The authors empirically determine that the musical thinking of students is based on advanced abilities in terms of the sense of the whole – the sense of shape, emotional response to music, and the sense of the logical development of the piece of music. Dominants in musicians’ musical thinking are the emotional response to music, musical-creative imagination – insight into the essence of the musical image, and high cognitive activity.